Peculiar association of pulmonary embolism with evolved inferior wall myocardial infarction - Selvam, Nandha kumar; Kumar, Dhilipan; Kandasamy, Tharagaram (Indian Journal of Case Reports, 2022)
Inferior wall myocardial infarction (MI) is one of the common straightforward cardiac conditions in the emergency department (ED) but inferior wall MI masquerading pulmonary embolism (PE) is extremely rare and can be missed if not evaluated promptly in ED. Misdiagnosis of PE is associated with high mortality. Here, we report a case of a 67-year-old male who was admitted to the ED and has been diagnosed with evolved inferior wall MI based on his clinical presentation and electrocardiogram. Later, he developed syncope following which he was reassessed and evaluated for the other possible conditions. Bedside echocardiography findings raised suspicion for PE, which was further confirmed by computed tomography pulmonary angiogram (CTPA). The patient underwent successful thrombolysis and was scheduled for an elective coronary angiogram. This case report highlights the importance of clinical presentation and the benefits of bedside echocardiography that helped in suspecting the association of PE with evolved inferior wall MI.